The cytochrome 11B2 aldosterone synthase gene CYP11B2 (RS1799998) polymorphism associates with chronic kidney disease in hypertensive patients - Dzhuryak, V.; Sydorchuk, L.; Sydorchuk, A.; Kamyshnyi, O.; Kshanovska, A.; Levytska, S.; Knut, R.; Sheremet, M.; Ivashchuk, M.; Petrynych, O.; Kazantseva, T.; Nikyfor, L.; et al. (My University, 2020)
Renin-angiotensin aldosterone system (RAAS) holds a crucial role in blood pressure regulation. Aldosterone is encoded by the cytochrome 11B2 aldosterone synthase gene (CYP11B2). The study aim was to analyze the association of Chronic Kidney Disease (CKD) with allelic polymorphism of the CYP11B2 at position -344 (-344C/T) in the promoter in patients with essential arterial hypertension (EAH). 72 subjects with EAH and target-organ damaging (2nd stage), moderate, high or very high cardiovascular risk were involved in the case-control study. Among them, 70.83% (51) females and 29.17% (21) males, mean age 59.87±8.02 yo; disease duration from 6 to 25 years. CKD was determined by the National Kidney Foundation recommendations (Kidney Disease: Improving Global Outcomes (KDIGO), 2012) after glomerular filtration rate (GFR) decline <60 ml/min/1,73 m2 for over 3 months (by CockroftGault formula and CKD-EPI for Cystatin-C and Creatinine serum levels depending on gender). CKD was diagnosed in 29 persons. Control group consisted of fourty-eight practically healthy individuals of relevant age. Gene polymorphism of aldosterone synthase gene CYP11B2 (-344C/T) was examined by polymerase chain reaction (PCR). The probability of EAH in the observed population increased 1.49 times in T-allele carriers of CYP11B2 gene, but only in females [OR=1.90; 95%CI:1.02-3.54; р=0.029], with contrary decreasing in C-allele women (p=0.041). Moreover, T-allele increased probability of CKD (GFR<60 ml/min/1,73m2 ) in hypertensive population 1.48 times [OR=1.86; 95%CI:1.01-3.58; р=0.049], especially in T-allele females 1.53 times [OR=6.51; 95%CI:1.39-30.60; р=0.007] with low CKD risk in T-allele males [OR=0.15; 95%CI:0.03-0.72; р=0.009], respectively. Furthermore, some predictors like Diabetes, the 2nd and 3rd grades Obesity, and the 3rd grade of Blood Pressure elevation escalated the risk of CKD 2.4, 2.08-2.32 and 2.91 times, accordingly (p<0.05). Thus, aldosterone synthase gene CYP11B2 (-344C/T) associated with EAH. T-allele increased risk of CKD in hypertensive population, especially in females.
Keywords: CYP11B2 gene (-344C/T); Chronic Kidney Disease; Arterial Hypertension; Risk; Aldosterone